2018
DOI: 10.1590/1809-4392201703340
|View full text |Cite
|
Sign up to set email alerts
|

First phytochemical description of essential oils from Piper cachimboense (Piperales, Piperaceae)

Abstract: Piper cachimboense is recorded only for the Amazon region of Brazil and Colombia, and the objective of this study was to report the first phytochemical assessment of the composition of the essential oils (EOs) from this species collected in the Amazon rainforest, in Novo Progresso, Pará State, Brazil. Samples of leaves were subjected to hydrodistillation in a Clevenger-type apparatus. The chemical identification was carried out by gas chromatography. The yield of oils was of 11.03 ± 5.94% for fresh leaves, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In a study by Fidyt and collaborators 16 , α-pinene was identified as one of the main components of essential oils of Piper species, corroborating the results of the present research. On the other hand, a study by Krinski et al 23 identified β-pinene, limonene, (E)caryophyllene, and caryophyllene oxide in the composition of the essential oil of Piper mosenii, indicating that variations in the constitution of this species may occur. In fact, consistent evidence has demonstrated that quantitative and qualitative changes in the chemical composition of essential oils might arise under the influence of seasonal, environmental, and technical factors 24 .…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Fidyt and collaborators 16 , α-pinene was identified as one of the main components of essential oils of Piper species, corroborating the results of the present research. On the other hand, a study by Krinski et al 23 identified β-pinene, limonene, (E)caryophyllene, and caryophyllene oxide in the composition of the essential oil of Piper mosenii, indicating that variations in the constitution of this species may occur. In fact, consistent evidence has demonstrated that quantitative and qualitative changes in the chemical composition of essential oils might arise under the influence of seasonal, environmental, and technical factors 24 .…”
Section: Resultsmentioning
confidence: 99%
“…The paddy bug (Oebalus poecilus), a late-season rice pest, is one of the most destructive rice pests currently in Guyana, and the Integrated Pest Management (IPM) system is used to control it since one method of control has proven to be ineffective to completely control this particular pest. With both adults and nymphs feeding on the paddy grains, the damage they wreak has a negative effect on the harvested paddy [2] [3] [4] [5]. Infested panicles lead to wind grains, malformation, and discoloration of grains, resulting in lower yields, reduced quality, and brittleness, which increase the breakage on milling [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fazolin et al (2006) highlighted the variety of compounds from mixed routes (chiquimate/acetate) generating phenylpropanoic aromatic compounds (lignans and neolignans), as well as terpenes and flavonoids. For this reason, the composition of essential oils of different species of Piperaceae in Brazil has been researched under several biological and biotechnological aspects (Mesquita et al, 2005;Pereira et al, 2008;Guerrini et al, 2009;Oliveira et al, 2013;Girola et al, 2015;Krinski et al, 2018a).…”
mentioning
confidence: 99%